Development and validation of a physician dialogic risk communication instrument scale in Chinese online medical consultations on cancer treatment risks - Wenze Lu; Janelle Yorke; Yan Li; Winsome-Yuk-Yin Lam; Mengqi Li; Yule Hu; Cindy Sing Bik Ngai (Humanities & Social Sciences Communications)
Abstract Given the complexity and diversity of risks involved in cancer treatment, physician dialogic risk communication (PDRC), which refers to dynamic, responsive, and interactive communicative expressions that take into account patients’ perspectives, concerns, and emotions regarding risks, is gaining increasing prominence. However, there is a gap in the availability of a validated instrument scale to measure PDRC, particularly in the context of online medical consultations (OMCs), which are experiencing global growth with a significant surge in China. PDRC benefits from the accessible, flexible, private, and interactive processes offered by OMCs, which help patients manage treatment risks, monitor for recurrence, and address emotional needs. This study aims to develop and validate a new instrument scale for assessing the PDRC from patients’ perspectives in the Chinese OMCs for cancer treatment risk communication. An eight-item instrument scale was developed using the Delphi method, translated into simplified Chinese, and its content and readability were confirmed through expert cross-checks and patient interviews. The scale was subsequently validated with 250 eligible participants from the Chinese mainland. The scale demonstrated high content validity, internal reliability (Cronbach’s α = 0.801), homogeneity (corrected item-total correlations: 0.430–0.570), and a robust one-dimensional structure (eigenvalue > 1, loadings: 0.563–0.706). Over 90% of participants rated items as critical, with three items deemed ‘very important’ significantly more often. This study contributes to physician-patient communication literature and risk communication practices. Researchers could use this scale to evaluate the adherence of OMCs to PDRC as a physician communication quality indicator, adapt it for linguistically and culturally diverse populations, and apply it to guide physicians in addressing patient concerns through dialogic and patient-centered communication across online healthcare settings. Physicians can refer to the scale to enhance their communication skills during OMCs, foster patients’ positive psychological outcomes, and encourage patients’ proactive behaviors in cancer care and beyond.